Weather and Crime—Cautious evidence from South Africa - Jörg Ankel-Peters; Anna Bruederle; Gareth Roberts (Q Open, 2022)
South Africa has one of the highest crime rates in the world. This paper examines the effect of weather shocks on various types of crime. Using a 12-year panel data set at a monthly resolution on the police ward level, we observe a short-term effect of temperatures on violent crime. Furthermore, we find evidence for the medium-term effect of weather on crime via droughts. Yet, effect sizes are subtle in both cases and we also emphasize often neglected but well-documented limitations to the interpretability of weather data and weather-induced mechanisms. Recognizing these limitations, we conclude with a cautious interpretation of our findings to inform police deployment strategies.
Keywords: C33; O55; Q54; R11; 330; South Africa; Weather; Crime; Income shocks